A model of socio-technical systems enhancing creativity - Chaiyasoonthorn, Womchanok; Suksa-Ngiam, Watanyoo (My University, 2017)
Information system (IS) research has not yet been used to explain individual and team creativity in organizations. It is already a fact that creativity is important not only for individuals but also for organizations. However, although we deem creativity as important, we have not yet connected it with the current findings in IS theory. In this research, the objective is to draw a connection among theories in IS and psychology to explain creativity in organization, which is based on the interaction among information technology and social systems. We then present key propositions and constructs as a form of a proposed theoretical framework. We suggest how to develop these constructs and test future hypotheses. We will use exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) during the process of instrumental development. Structural equation modeling (SEM) will be used in the future research for hypothesis testing. We also discuss the expected contribution of this paper to information systems.
Keywords: creativity; information technology; innovation; socio-technical systems